A Production planning study on Ponderosa Leather Goods Company, Inc. - Dunuan, Lara Mia; Inumerable, Jennifer; Poblete, Natalie Ian. (Diliman, Quezon City College of Engineering, 2003)
Ponderosa Leather Goods Company, Inc., the company under study, is a manufacturer of a wide range of baseball gloves, hockey gloves, and mitts. It is the company's goal to satisfy their customers' demands by producing high quality gloves. To do so, the company has to run an efficient and effective production system. In line with improving the production and operations of PLGCI, a study was conducted to improve the systems of the said company. The study also aims to identify the major problem areas of the company and to provide the appropriate analyses and recommendations to further improve the operations management system of the company. Documentation of the company's capacity planning, forecasting methods, inventory system, supply chain management, and aggregate plans were done by the team to evaluate the existing system of the company. After the documentation of the system, the three major problem areas were identified. These are (1) deviation of forecast from actual demand, (2) high equipment maintenance cost, and (3) high overtime cost. The inefficient forecasting technique was due to the naive approach that the company currently employs. Since this approach proves to be insufficient, the team recommended the use of the Multiplicative Seasonal Model, which is suited for demand behavior that is seasonal. This technique yields the best tracking signal and mean absolute deviation for the baseball gloves, hockey gloves, and mitts. The second problem area is the high equipment maintenance cost. The team proposed the implementation of a preventive maintenance scheme, which results to lower cost compared to the current plan that the company uses. High overtime cost is the third problem area. The team recommended an additional shift during the peak months for the finger sewing, palm sewing, and binding section in the A3 line.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Ponderosa Leather Goods Company Incorporated; Leather industry; Production engineering